A daughter's choice - Irvin, Kelly (Heart of the Amish, 2025)
"Henrietta Is Set Against Love. Full of faith, hope, and romance, this series takes you into the Heart of Amish Country. Henrietta Miller loves animals -- especially her goats. She wants to marry and have children someday, but right now her goal is to have her own business selling snacks made from goat's milk and goat's soaps. Against her the wishes of her father -- who's also the bishop -- she applies for a job as a veterinary assistant to earn money. Then newcomer Nicholas Byler snatches the job out from under her -- or so it seems to Hen. Now Nicholas is treating Hen's beloved animals as if he knows more than her. Hen turns her frustrations toward expanding her business to include wool-producing goats, even while her aunt hatches matchmaking plans -- with Nicholas Byler, no less."--